THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT ON EMPLOYEE WORK PRODUCTIVITY IN THE ADIDAS DIVISION AT PT XYZ - Deva Silviana; Moh. Sutoro; Suflani Suflani (Yayasan Education and Social Center, 2026)
Employee productivity is an important factor for manufacturing companies in achieving production targets. In the Adidas Division of PT XYZ, production achievement still fluctuates, indicating that organizational culture and work environment need to be examined as factors affecting employee productivity. This study aims to determine the effect of organizational culture and work environment, both partially and simultaneously, on employee productivity in the Adidas Division of PT XYZ. This research uses a quantitative approach with a survey method. The population consisted of 200 employees in the Adidas Division, while the sample consisted of 146 respondents determined using the Slovin formula with a simple random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 27. The results show that organizational culture has a positive and significant effect on employee productivity with a t-value of 6.978 and a significance level of 0.000. The work environment also has a positive and significant effect with a t-value of 2.694 and a significance level of 0.008. Simultaneously, organizational culture and work environment have a significant effect on employee productivity with an F value of 175.318 and a coefficient of determination of 71.0%. The conclusion of this study shows that organizational culture and work environment play an important role in improving employee productivity. Therefore, companies need to strengthen organizational culture and create a conducive work environment to support increased employee productivity.